Questionnaires measuring movement behaviours in adults and older adults: Content description and measurement properties. A systematic review - Rodrigues, B (2022)
Background Sleep, sedentary behaviour and physical activity are constituent parts of a 24h period and there are several questionnaires to measure these movement behaviours, the objective was to systematically review the literature on content and measurement properties of self- and proxy-reported questionnaires measuring movement behaviours in adults and older adults. Methods The databases PubMed, CINAHL, PsycINFO and SPORTDiscus were systematically searched until April 2021. Articles were included if: the questionnaires were design for adults and older adults; the sample size for validity studies had at least 50 participants; at least, both validity and test-retest reliability results of questionnaire that were developed specifically to measure the amount of sleep, sedentary behaviour or physical activity, or their combination were reported; and articles had to be written in English, Spanish, French, Portuguese, German, Italian or Chinese. Findings and conclusions Data extraction, results, studies’ quality, and risk of bias were evaluated using the Consensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines. Fifty-five articles were included in this review, describing 60 questionnaires. None of the questionnaires showed adequate criterion validity and adequate reliability, simultaneously; 68.3% showed adequate content validity. The risk of bias for criterion validity and reliability were very low in 72.2% and 23.6% of the studies, respectively. Existing questionnaires have insufficient measurement properties and frequent methodologic limitations, and none was developed considering the 24h movement behaviour paradigm. The lack of valid and reliable questionnaires assessing 24h movement behaviours in an integrated way, precludes accurate monitoring and surveillance systems of 24h movement behaviours. © 2022 Rodrigues et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.